The influence of Product Quality, Product Innovation and Electronic Word of Mouth on Repurchase Intention is mediated by Customer Satisfaction in the Marketplace(Case study of Indomaret Semarang branch employees) - Gitaringga, Putri Nova; Kurniawan, Bayu; Indiworo, Rr Hawik Ervina (Universitas Nusantara PGRI Kediri, 2024)
Research aim :This research was conducted to test the influence of product quality, product innovation and electronic word of mouth on repurchase interest mediated by customer satisfaction in the marketplace. Design/Methode/Approach : Approach in this case the research uses quatitative with primary data types and data collection using literature studies and data obtained from distributing Googleform questionnaires. The population in I was employees of the semarang branch of Indomaret, totaling 2.792 people. In this study, it was calculated using the slovin formula to obtain a score of 350 employees. The technique used is a probability sampling technique with a simple random sampling method and the criteria are employees of semarang branch of Indomaret who are marketplace uses. The data analysis technique in this research uses (SEM) structural equation modeling or SmartPLS. Research Finding : Based on research that has been conducted, it was found that product quality has no effect on repurchase interest, product innovation, electronic word of mouth and customer satisfaction have a positive and significant effect on repurchase interest, product quality has no effect on customer satisfication, product innovation and electronic word of mouth have a positive and significant effect on customer satisfication, product quality and product innovation have no effect on repurchase interest which is mediated by customer satisfaction, electronic word of mouth has a positive effect on repurchase interest which is mediated by customer satisfaction. Research limitation : Limitations in time and energy so that this research not maximal.This research is far from perfect, so further researchwill be carried out hopefully better than before.